Effectiveness of Abstract – Visual – Concrete Approach in Enhancing Students’ Level of Conceptual Understanding and Mathematical Self-Efficacy - Reyes, Joseph D. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study was designed to transform mathematics instruction into a more engaging and practical learning experience, emphasizing real-world applications. The primary objective was to enhance conceptual understanding and mathematical self-efficacy among Grade 11 senior high school students in Statistics and Probability during the 2021-2022 academic year's second quarter. The findings demonstrated that mathematical self-efficacy positively correlates with conceptual understanding, with high-efficacy students showing greater confidence and positive attitudes toward mathematics. The Abstract-Visual Representation-Concrete (A-V-C) instructional approach proved effective in teaching Pearson product moment correlation and regression analysis. This method progresses from abstract concepts through behavioral modeling to exploratory concrete experiences, enabling students to develop comprehensive understanding through structured, hands-on learning.